Strategy Analysis of Regional Tax Increase and Regional Retribution of Banda Aceh City in the New Normal Era Covid Pandemic 19 - Rizka Rizka (Budapest International Research and Critics University, 2020)
This study aims to analyze the strategy carried out and analyze the problems in determining the strategy as an effort to increase local revenue during the New Normal Pandemic Covid 19. The object of this research is the strategy for increasing local tax revenues and levies prepared by the Banda Aceh City Government. Meanwhile, the subjects in this study are the Head of the BPKK Office, the Secretary of the BPKK, the Head of Billing, the Head of Data Collection, and the Head of Accounting who are divided into duties and obligations to participate in developing strategies for increasing regional revenues. This research is a descriptive study, while the approach is a qualitative approach. Data collection was carried out in two ways, namely library data collection and field data collection. The results showed that; (1) Problems that exist in Pemko Banda Aceh are fiscal dependence on the Central Government, not optimal exploration of regional potential, inefficient performance of regional financial management and weak systems and socialization. (2) The strategy adopted by Pemko Banda Aceh is to implement intensification and extensification efforts. (3) Problems faced in realizing the strategy for increasing regional revenue include unattainable organizational goals, lack of coordination with other parties, weak supervision including instruments, lack of use of information technology, and limited quality of human resources.